MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN IBU KADER DALAM MENGOLAH TEMPE SEBAGAI SUMBER NUTRISI BERKUALITAS - Mulyani, sri (Poltekkes Kemenkes Riau, 2025)
Tempe is a nutritious food that is easily digested by all age groups. The development of innovative food products provides many benefits, including increasing knowledge of protein consumption at a lower cost and with easier processing. Another benefit is enhancing the economy through the development of various tempebased snacks, as well as promoting dietary variety among different age groups. Tempe is made from fermented soybeans. The nutritional composition of tempe, including protein, fat, and carbohydrates, is higher than that of soybeans. The development of innovative food products has the potential to improve health, stimulate economic growth, and promote dietary diversity across age groups. However, many people, especially housewives and community health volunteers, do not fully understand the potential and benefits of tempe-based products in daily diets. Therefore, efforts are needed to provide education and training to empower them in processing tempe into a high-quality source of nutrition for families and communities. The expected outcomes of this community service activity include the creation of tempe-based product recipes and publication in a community service journal.